(untitled) (Experimental biology, 2017)
Cyanobacteria are modern and promising producers of biodiesel. Despite the fact that there is a large amount of knowledge about the high accumulation of lipids by individual strains of cyanobacteria at the laboratory level, the issue of lipid extraction, allowing to extract the maximum amount of intracellular lipids from biomass, remains open. Cyanobacterium sp. IPPAS B-1200 is a strain of cyanobacteria isolated from Balkhash lake. According to previous studies, the analysis of the fatty acid composition of total cellular lipids showed that the strain Cyanobacterium sp. has a high content of myristic (14: 0) and myristoleoleic acids (Δ9-14: 1) (30% and 10% of the sum of fatty acids, respectively). Such an FA composition is a rarity for cyanobacteria, and at the same time, it is 14: 0 and Δ 9-14: 1 that FA s are potential target products for biofuel production. The article considers the process of lipid extraction from cyanobacteria using various organic solvents. A comparative analysis of the methods of lipid extraction from the biomass of the cyanobacterium strain Cyanobacterium sp. IPPAS B-1200. Experimental data on the yield of the lipid fraction during extraction using various organic solvents are indicated. The following compositions were used as extractants: Chloroform-methanol 2/1; Chloroform-methanol 1/2; Hexane-isopropanol 3/2. It was found that lipid extraction with methanol/chloroform 2/1 (Bligh and Dyer method) gives the highest lipid yield and is 9% of the dry matter of the biomass of the strain under investigation. The obtained data make it possible to consider the Bligh and Dyer method to be optimal. Thus, research directed on study of possibilities of increasing lipid production and providing the good quality raw material will allow to find ways for solution of problem of obtaining the third generation alternative biofuel.